STUDI PEMETAAN INDUSTRI KREATIF DI LINGKUNGAN LAHAN BASAH PROPINSI KALIMANTAN SELATAN - Sarwani; Kadir (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
The purpose of this study is to map the creative industries in the wetlands in the province of South Kalimantan. Specifically, the purpose of this study was to determine the potential, the bottleneck problem and strategize the development of creative industries Data analysis method used in this research is descriptive quantitative and qualitative analysis. The analysis technique used ie scoring, cross tab analysis, and SWOT analysis to determine the position of the strengths, weaknesses, opportunities and constraints. Mapping results indicate that there is excellent potential or core competencies in the area of creative industries in South Kalimantan, namely handicrafts, architecture, art and antiques market. Some of the key issues in the development of creative industries in South Kalimantan province, the capital, production, and business management, and marketing. The concept and strategic approach to the development of creative industries in South Kalimantan province namely the need to 1) the strengthening of the capital, 2) an increase in machinery and equipment production in some industries, 3) human resource development through training, business management, internships, promotion and marketing information products, 4) increase the competitiveness of the industry through education and training activities of design, trademarks and registration of industrial patents, 5) establish partnerships and collaboration with academia, bureaucracy and government, and 6) carried out a study on some of the excellent products of creative industries gradually.